METAPHYLAXIS OF NEPHROLITHIASIS: A PATHOGENETIC APPROACH USING MEDICINAL PLANTS AND LOCAL REMEDIES FROM SOUTHERN KAZAKHSTAN - M. Baydybekov M.; B. Aitbayuly; A. Yernazarov; B. Baydybekov (Yassawi Journal of Health Sciences, 2026)
Recurrent nephrolithiasis remains one of the most challenging problems in contemporary urology. This study presents a comprehensive, pathogenesis-based approach to metaphylaxis (prevention of recurrent stone formation) using medicinal plants, traditional beverages, and acidic mineral waters endemic to Southern Kazakhstan. Over a 12-year period, 500 patients with various forms of urolithiasis were treated using protocols developed based on the proteolysis–ion theory of stone formation. The study evaluated the effects of galenic preparations from camel thorn (Alhagi pseudalhagi), Turkestan bedstraw (Galium turkestanicum), kumiss (fermented mare's milk), and acidic mineral waters (Chelkar and Zhosalin springs) on urine pH, proteolytic activity, and diuresis—the primary risk factors for urolithiasis. Treatment regimens were differentiated according to stone type: urate, calcium oxalate, and phosphoric acid nephrolithiasis. Results demonstrated a reduction in recurrence rates to 13% in the treatment group versus 62.7% in the control group, with a 1.5-fold reduction in disability rates. This evidence-based approach provides practical therapeutic recommendations suitable for implementation in resource-limited settings and offers a model for integrating traditional medicine with modern urological practice.